VCO AND ALOE VERA TO CURE DIAPER RASH IN BABIES 0-2 YEARS OLD - Mei Lia Nindya Zulis Windyarti; Yuni Fitri Prestian; Dyah Ayu Wulandari (Jurnal Smart Kebidanan, 2024)
Background: Diaper rash is dermatitis due to irritation in the form of skin manifestations caused by various things. In Indonesia, as many as 22 million toddlers in Indonesia, around 1/3 of the number of these babies experience diaper rash. Treatment of diaper rash can be done with non-pharmacological therapy, namely by using Aloe vera because it has a therapeutic effect as an anti-inflammatory and antimicrobial and has safety in dealing with diaper rash because it contains alpha-bisabolol. Another alternative that can be used to prevent or treat diaper rash is coconut oil (coconut oil) for skin health and anti-microbial. Objective: To determine the effectiveness of VCO and Aloe vera in accelerating the healing of diaper rash in infants 0-2 years. Research Methods: Type of quantitative research with a quasi-experimental approach and a pretest-posttest design. The population in this study were infants aged 0-2 years who had diaper rash. Research Results: Based on the results of the Mann-Whitney test, the p-value of the Mann-Whitney test was obtained, respectively above 0.05 (p>0.05), namely 0.658; 0.593; and 0.483. This insignificant difference can also be interpreted that Aloe vera and VCO have relatively similar effectiveness in healing diaper rash inflammation. Conclusion Aloe vera and VCO have the same effectiveness in healing inflammatory diaper rash.